Energy dependent relative cross sections in carbon 1s photoionization. Issue 15 (January 2020) - Travnikova, O; Patanen, M; Söderström, J; Lindblad, A; Kas, J J; Vila, F D; Céolin, D; Nicolas, C; Marchenko, T; Goldsztejn, G; Journel, L; Guillemin, R; et al.
Synopsis: We demonstrate that the possibility of monitoring relative photoionization cross sections over a large photon energy range extending to hard x-rays allows studying and disentangling shake processes and intramolecular inelastic scattering effects. An "EXAFS"-type of oscillatory behaviour of the relative C 1 s cross sections is observed in a wide photon energy range up to 1 keV due to multiple intramolecular elastic scattering of the photoelectron. These effects are also present in solids and constitute a significant part of all elastic and inelastic scattering effects occurring in solids.